Peran Krusial Orang Tua Terhadap Perkembangan Iman Anak Katolik - Mesriani Alosya Sigiro (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The development of Catholic children's faith is greatly influenced by the role of parents as role models and primary educators. In the family, parents are responsible for introducing the values ​​of Catholic faith and traditions through teaching, religious practices and constructive discussions. This research reveals that parental involvement in children's spiritual lives not only strengthens the foundations of faith, but also shapes children's character and morals. Through various methods, such as praying together, attending mass, and reading the Bible, parents can create an environment that supports the growth of faith. The research results show that children who receive strong spiritual support from their parents tend to have a higher commitment to their Catholic faith in the future. Therefore, the role of parents is very crucial in forming and maintaining their children's faith.